Hukum antar golongan. Interaksi fiqh Islam dengan syariat agama lain - SHIDIEQY, Tengku Muhammad Hasbi Ash (Pustaka Riski Putra, 2001)
Hukum antar golongan. Interaksi fiqh Islam dengan syariat agama lain